2001
DOI: 10.3109/00207450109149736
|View full text |Cite
|
Sign up to set email alerts
|

HIV Adolescents Show Improved Immune Function Following Massage Therapy

Abstract: HIV+adolescents (M CD4=466 mm3) recruited from a large urban university hospital's outpatient clinic were randomly assigned to receive massage therapy (n=12) or progressive muscle relaxation (n=12) two-times per week for 12 weeks. To assess treatment effects, participants were assessed for depression, anxiety and immune changes before and after treatment the 12 weeks treatment period. Adolescents who received massage therapy versus those who experienced relaxation therapy reported feeling less anxious and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 16 publications
(15 reference statements)
5
89
1
7
Order By: Relevance
“…It is potentially very important, especially in terms of the apparent effect size, to cancer patients if an improvement in their immune system functioning can help to protect them from infections during the course of their chemotherapy. However, in contrast to other studies, no significant differences were found for WBCs in general or in the other measures of immune system functioning involving various specific different types of WBCs: for example, Field et al (2001) found that massage increased WBCs and neutrophils, Diego et al (2001) reported that it increased CD4 cells and the CD4/CD8 ratio, and Kuriyama et al (2005) found that it increased the CD8 cell count. Differences between the results of the present and other studies may be explained in terms of differences in the populations studied, in the frequency, length, spacing and number of massage sessions, and in the massage procedure itself.…”
Section: Discussioncontrasting
confidence: 41%
“…It is potentially very important, especially in terms of the apparent effect size, to cancer patients if an improvement in their immune system functioning can help to protect them from infections during the course of their chemotherapy. However, in contrast to other studies, no significant differences were found for WBCs in general or in the other measures of immune system functioning involving various specific different types of WBCs: for example, Field et al (2001) found that massage increased WBCs and neutrophils, Diego et al (2001) reported that it increased CD4 cells and the CD4/CD8 ratio, and Kuriyama et al (2005) found that it increased the CD8 cell count. Differences between the results of the present and other studies may be explained in terms of differences in the populations studied, in the frequency, length, spacing and number of massage sessions, and in the massage procedure itself.…”
Section: Discussioncontrasting
confidence: 41%
“…Surprisingly, there were no differences on the growth measures as there have been in other long-term studies. Only 5% of the infants were infected despite the uniform exposure to their HIV-infected mothers which may relate to the massage saving CD4 cells (typically attacked by the HIV virus) as has happened in other HIV studies (Diego, HernandeReif, Field, Friedman & Shaw, 2001). Another possibility is that the massage increased natural killer cell activity, as it has with preterm newborns (Ang et al, 2012), and natural killer cells, in turn, warding off HIV cells.…”
Section: Full-term Newborn Massage Therapy Effects (See Table 2 For Ementioning
confidence: 99%
“…Furthermore, it was reported in the case of HIV-positive patients that twenty 45-min massages in one month or twice a week for 12 weeks significantly increased NK cell numbers and cytotoxicity 6,19) . The results in the present study were different from those, this difference may due to the short term effect of massage in the present study, while the long-term effects in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…There is a letter about immunological effects of one time 1hr massage therapy on 9 healthy female medical students and they found increase in total WBC counts and increase in NK cell activity after the massage 5) . In addition, there have been three reports on the change in the immune functions of HIV-positive patients caused by massage [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%